PERAN GURU SEBAGAI FASILITATOR DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK DI SD INPRES NUNBAUN DELHA KOTA KUPANG - Taty R. Koroh; Andriyani A. D. Lehan; Ferderika M. Moykari (Journal of Character and ELementary Education, 2023)
This research aims to know teacher role as a fasiliator in increasing students learning interst is at elementary school Inpres Nunbaun Delha, Kupang City. The method used is qualitative description, the data were collected used observation, interview and documents. The data analized use data reduction, data presentation, and data drawing conclusions.This research was conducted at elementary school Inpres Nunbaun Delha, Kupang City. The subject of this research is IV, V, VI grade students. Based on the results of research in increasing students' interest in learning at elementary school Inpres Nunbaun Delha, Kupang City, the teacher tries to carry out her role as a facilitator, namely: the teacher listens and does not dominate during learning activities, the teacher is patient by allowing students to learn actively and independently, the teacher respects and humble for each student's work, the teacher is equal to students, the desire to learn by determining the topic without telling the material to students, the teacher does not try to lecture students during learning, the teacher is authoritative, the teacher is open and the teacher is positive during learning.Based on the discussion above, it can be concluded that the teacher as facilitator means: a) the teacher listens and does not dominate; b) the teacher is patient; c) the teacher respects and is humble; d) teachers act as equals; e) desire to learn; f) the teacher does not try to lecture students; g) the teacher is authoritative; h) teachers are open and; i) the teacher is positive.